Preparation and electrical behaviour of BaCeO3 ceramics - Boothrawong N. (2017)
© 2016 Trans Tech Publications, Switzerland. Barium cerate (BaCeO 3 ) ceramics were synthesized via a solid-state reaction technique. Pure phase perovskite powders were obtained at a calcination temperature of 1200 ?C. BaCeO 3 ceramics were fabricated from the calcined powder and their properties were investigated. XRD data of the ceramics was consistent with an orthorhombic symmetry. The microstructural analysis indicated that grain sizes of the ceramics increased with increasing sintering temperature. The dielectric constant of the samples slight changed over a very wide range of temperature. All ceramics showed very good dielectric performance where the ceramics sintered at 1450 oC showed the highest dielectric constant.